Clinicopathological Study of Change of Voice - Md Arifuzzaman, -; Fattah, Shaikh Nurul; Islam, Mohammad Nazrul; Hasan, Md Mehedi; Islam, Md Monirul; Tabassum, Chowdhury Tamanna; Monira, Shirajum; Mohammad Tanvir, Sardar; Mohammad Farhad, - (Journal of Dhaka Medical College, 2021)
Background: Change of voice is one of the common complaints in ENT practice and hoarseness of voice is the commonest symptom of changed voice quality. Hoarseness is invariably the earliest manifestation of conditions directly or indirectly affecting the voice apparatus. Though most common causes of hoarseness are benign and vocal abuse is the commonest among them, but we should always investigate for more sinister pathology like malignancy. Objectives: To find out the symptoms, signs and pathological incidence, leading to change of voice for early diagnosis and interventional purpose. Methods: Total 87 patients of change of voice, studied in 06 months duration from 1st January 2016 to 30th June 2016 in the Department of ENT & Head-Neck Surgery, Dhaka Medical College Hospital, Dhaka. The cases were selected according to the eligibility criteria by purposive sampling. Then the data were collected by the active participation of the patients interviewed by the preformed proforma of data collection sheet. Results: Maximum number of cases of change of voice were due to carcinoma larynx (37.93%), then chronic laryngitis (20.99%), followed by vocal cord nodules (19.54%) and vocal cord polyps (8.05%.). Laryngopharyngeal reflux was found in 45.95% patients of chronic laryngitis. Males were affected more than females (1.81:1). Most of the patients were in the age group of 21 to 50 years. Peak incidence was in the 4th decade. Labourers/ daily wage earners formed the predominant group. Majority of patients were from low socioeconomic class. Smoking, vocal abuse, smoking and infections were the common predisposing factors. Conclusion: Hoarseness of voice is just a symptom with a very diverse etiology. The etiological data varies in different geographical location and from one center to other, so every case should be carefully and thoroughly evaluated to know the diagnosis and underlying pathology for early and prompt management. J Dhaka Medical College, Vol. 29, No.2, October, 2020, Page 116-125